Performance assessment of direct injection compressed natural gas vehicle at different injection pressures using speed-sweep test method - Mohd Fadzil, Rahim; Abdul Aziz, Jaafar; Rizalman, Mamat; Zahari, Taha
This paper presents an experimental study on a high-pressure direct injection compressed natural gas engine (HPDI-CNG) vehicle using speed-sweep test method. The objective of this work is to assess the performances of the HPDI-CNG after installation of a new DI configuration on the engine. The gas direct injectors which were converted from gasoline direct injection (GDI) unit injector are side-positioned on an inline 4-cylinder 4 stroke CAMPRO 1.6 engine with minimal cylinder head modification. The original electronic control unit was replaced with a programmable HALTEC controller and the engine was set to operate in bi-fuel mode. The HPDI-CNG vehicle prototype is tested on chassis dynamometer by using speedsweep test procedure. The tests were carried out in vehicle simulation mode for acceleration from 20 mph to 40 mph based on the ramp input from idle-speed to wide-open throttle opening. The responses of the engine were recorded as transient output data. The HPDI-CNG engine output produced lower performances compared to the same engine with gasoline port injection. This is demonstrated by the maximum engine speed, brake torque and brake power which are recorded to be 2800 rpm, 63 Nm, and 17 kW respectively. It can be concluded that the use of sidepositioned direct injector of HPDI-CNG system is unable to increase engine performance if compared to a gasoline port gasoline engine. Moreover, the use of throat- geometry has resulted in a lower performance of HPDI-CNG engine compared to a standard CNG-DI engine. The main factor which affected the HPDI-CNG engine is the ability of the system to deliver sufficient fuel mass at the correct amount and timing as well as the insufficiencies of the air supplies to oxidize the fuel completely